DIPG-41. DISSECTING THE MECHANISTIC BASIS FOR ACVR1 AND PIK3CA MUTATION CO-OCCURRENCE IN DIFFUSE MIDLINE GLIOMAS USING GENETICALLY ENGINEERED MOUSE MODELS. (4th December 2020) - Wu, Annette; Mak, Tak; Fortin, Jerome
Abstract: Diffuse midline gliomas (DMGs) are aggressive childhood brain tumors with a dismal prognosis. Most of these tumors carry K27M mutations in histone H3-encoding genes, particularly H3F3A and HIST1H3B . In addition, activating mutations in ACVR1 and PIK3CA co-occur in a subset of DMGs. To understand how these lesions drive the development of DMGs, we generated genetically engineered mouse models in which Acvr1 G328V, Hist1h3b K27M, and Pik3ca H1047R are targeted to the OLIG2-expressing cell lineage. Animals carrying Acvr1 G328V and Pik3ca H1047R, with ("AHPO") or without ("APO") Hist1h3b K27M, developed high-grade diffuse gliomas involving midline and forebrain regions. Neither Acvr1 G328V nor Pik3ca H1047R drove tumorigenesis by themselves, but Acvr1 G328V was sufficient to cause oligodendroglial differentiation arrest, pointing to a role in the earliest stages of gliomas formation. Transcriptomic analyses of AHPO and APO tumors indicated a predominantly proneural and oligodendrocyte precursor-like gene expression signature, consistent with the corresponding human pathology. Genes encoding transcription factors (TFs) with dual roles in controlling glial and neuronal differentiation were upregulated in tumors. Some of these genes were mildly induced by Acvr1 G328V alone. Functional experiments using CRISPR/Cas9-mediated gene editing in patient-derived cell lines confirmed a role for some of these TFs in controlling DMG cell fitness. Overall, our results suggest that Pik3ca H1047R consolidates Acvr1 G328V -induced glial differentiation arrest to drive DMG development and progression.